2015
DOI: 10.1093/mnras/stv1038
|View full text |Cite
|
Sign up to set email alerts
|

From the ‘blazar sequence' to unification of blazars and radio galaxies

Abstract: Based on a large Fermi blazar sample, the blazar sequence (synchrotron peak frequency ν peak versus synchrotron peak luminosity L peak ) is revisited. It is found that there is significant anti-correlation between ν peak and L peak for blazars. However, after being Doppler corrected, the anti-correlation disappears. The jet cavity power (P jet ) is estimated from extended radio luminosity. So it is free of beaming effect. We find that there are significant anti-correlations between P jet and beam-corrected ν ′… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…The distribution of the synchrotron peak luminosity as a function of the synchrotron peak energy for the EHBLs is presented in Figure 4. The synchrotron peak luminosity for the known EHBLs is obtained between 10 44 -10 45 erg sec −1 which is consistent with the values estimated for blazars in the range 10 43 -10 47 erg sec −1 [58,59]. The values of the synchrotron peak luminosity (∼ 10 45 erg sec −1 ) for Mrk 501 reported in the literature are in agreement with the values estimated for the EHBLs in the present study [52,57].…”
Section: Synchrotron Peak Luminositysupporting
confidence: 92%
“…The distribution of the synchrotron peak luminosity as a function of the synchrotron peak energy for the EHBLs is presented in Figure 4. The synchrotron peak luminosity for the known EHBLs is obtained between 10 44 -10 45 erg sec −1 which is consistent with the values estimated for blazars in the range 10 43 -10 47 erg sec −1 [58,59]. The values of the synchrotron peak luminosity (∼ 10 45 erg sec −1 ) for Mrk 501 reported in the literature are in agreement with the values estimated for the EHBLs in the present study [52,57].…”
Section: Synchrotron Peak Luminositysupporting
confidence: 92%
“…The observational differences are due to the anisotropic radiation caused by Doppler beaming effect (Urry & Padovani 1995). This unification scenario between blazars and radio galaxies has been verified in the literatures by many authors (Bai & Lee 2001;Xu et al 2009;Xiong et al 2015). In this paper, we compare the jet powers (extended jet emission) for BZCAT blazars and 3CR radio galaxies.…”
Section: The Unification Between Blazars and Radio Galaxiessupporting
confidence: 73%
“…Giommi et al (2012) concluded from their Monte-Carlo simulations that there are only two intrinsic blazar types, low-ionization sources consisting mostly of beamed Fanaroff-Riley type I (FR I) galaxies and high-ionization sources of mostly beamed FR II ones. Xiong et al (2015) also found an anti-correlation between jet power and beamcorrected synchrotron peak frequency of blazars and radio galaxies. Hervet et al (2016) approached the blazar classification using very-long-baseline-interferometry (VLBI) maps, resulting in three classes with different radio knot kinematics.…”
Section: Introductionmentioning
confidence: 69%